2013
DOI: 10.1371/journal.pone.0055625
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum C-Peptide Concentrations with Cancer Mortality Risk in Pre-Diabetes or Undiagnosed Diabetes

Abstract: BackgroundKnown associations between diabetes and cancer could logically be attributed to hyperglycemia, hypersecretion of insulin, and/or insulin resistance. This study examined the relationship between initial glycemic biomarkers among men and women with impaired fasting glucose or undiagnosed diabetes and cancer mortality during follow up.MethodsThe cohort included subjects aged 40 years and above from the Third National Health and Nutrition Examination Survey (NHANES III) with fasted serum glucose >100 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In a Norwegian long-term observational study (147) In line with this, c-peptide is associated with all-cancer mortality (168) and the outcome of breast cancer (169). Serum levels of c-peptide seem to increase the risk of breast cancer in postmenopausal women (170,171), but not in pre-menopausal women (172),(173).…”
Section: Grade 1 Tumors Often Follow Strong Expression Of Both Er Andmentioning
confidence: 87%
“…In a Norwegian long-term observational study (147) In line with this, c-peptide is associated with all-cancer mortality (168) and the outcome of breast cancer (169). Serum levels of c-peptide seem to increase the risk of breast cancer in postmenopausal women (170,171), but not in pre-menopausal women (172),(173).…”
Section: Grade 1 Tumors Often Follow Strong Expression Of Both Er Andmentioning
confidence: 87%
“…Hsu et al [17] found no associations between HbA 1c level and lung cancer mortality in a cohort of people with undiagnosed diabetes or impaired fasting blood glucose.…”
Section: Other Cancersmentioning
confidence: 96%
“…Eight studies focused on the relationship between HbA 1c and all types of cancer [10][11][12][13][14][15][16][17], and are summarized in Table 2. All studies were adjusted for age, sex and smoking status.…”
Section: All Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, studies have shown that the basal C-peptide level is significantly elevated among patients with metabolic syndrome and diabetes. Another recent study reported that the serum C-peptide level is independently associated with cardiovascular disease, cancer, and total mortality [14], [15]. However, currently, the metabolic characteristics of serum C-peptide are receiving considerable attention.…”
Section: Introductionmentioning
confidence: 99%